Molecular identification of arowana species based on cytochrome B and cytochrome C oxidase I (COI) / Maryam Zahedi Fard - Fard, Maryam Zahedi (2010)
Mitochondrial DNA (mtDNA) markers has been widely used to better resolve the taxonomic identification as well as display the genetic relatedness of different species and closely related fish. The highly cost ornamental fish, Asian arowana (Scleropages formosus) of family Osteoglossidae has different colored strains that are geographically distributed in different regions around Southeast Asia. The taxonomic classification of these different strains still remains unclear and disputable. The partial sequences of the cytochrome b and the DNA barcoding gene, cytochrome C oxidase were analyzed and assessed for molecular identification; to differentiate the colored varieties of this species. The results of this study indicated that there was lack of both COI and cytochrome mtDNA differentiation among the red and golden main varieties that it did not indicate emergence of new species. However, the partial sequences of the genes are sufficient to identify the species when compared to its closely related species as well as the green strains compared to other strains of the Asian arowana. In the future, more markers will be used to obtain a more concrete evidence to support the existence of a relationship among Arowana starians.